Good urodynamic practice adaptations during the COVID‐19 pandemic. Issue 6 (19th June 2020) - Hashim, Hashim; Thomas, Laura; Gammie, Andrew; Farullo, Giuseppe; Finazzi‐Agrò, Enrico
Abstract: Urodynamics testing forms the cornerstone of investigations when it comes to lower urinary tract dysfunction. It has to be done to the highest standards by following the International Continence Society Good Urodynamics Practice protocols. However, with the COVID‐19 pandemic, certain adaptations to the urodynamics procedure need to be considered especially when it comes to quality control. This article aims to define these adaptations to help urodynamicists in their daily practice.